Move to the edge, declare it center : practices and processes for creatively solving complex problems - Harper, Everett (John Wiley & Sons, Inc., 2022)
Lead your organizations, solve problems, and sustain your company's growth with effective practices for complex, uncertain, and unpredictable environments In Move to the Edge, Declare it Center, CEO, entrepreneur, and strategist Everett Harper delivers a powerful and pragmatic take on solving complex problems by, and making decisions through, uncertainty. You'll learn to discover insights quickly by experimenting, iterating, then building infrastructure to sustain your innovations in your teams and organizations. The author demonstrates a set of practices, processes, and infrastructure that addresses complex problems alongside a set of methods to systematize, scale, and share best practices throughout an organization. In the book, the author offers a new framework for leadership that's perfectly suited to an increasingly volatile, uncertain, and unpredictable world. You'll also get: Effective ways to make decisions in situations without complete information Strategies for sustaining your team through highly uncertain times Techniques for managing personal anxiety--a key leadership skill for the next decade Case studies of World Central Kitchen, COVID public health policymakers, and California wildfire responders illustrate the framework, while pragmatic playbooks about salary transparency, remote work, and diversity and inclusion will help leaders apply the framework in their own organizations. The author shares personal stories and winning strategies that help leaders maintain high performance, avoid burnout, and enable companies to thrive. Move to the Edge, Declare it Center is perfect for business leaders facing complex problems that require immediate decisions in the face of uncertain outcomes. It's also a must-read for anyone interested in modern leadership and looking for a way to help them make solid decisions with incomplete information.